Palynofacies Identification on Samples K4 and K5, Premban Profile, Jaten Formation, Dongko Area, Trenggalek, East Java - Istiana; Dedy Kurniadi Kurniadi; Muhammad Gazali Rachman (Engineering Faculty, UNSOED, 2025)
The northern region of East Java is known as Indonesia's largest oil and gas producer. The southern region also exhibits several potential petroleum system manifestations, such as shale outcrops that extract biogenic hydrocarbons in Dongko District, Trenggalek Regency. Identification of palynofacies/palynomacerals can be determined based on the kerogen composition of sedimentary rocks. This is crucial for more detailed exploration of hydrocarbon potential. The kerogen composition of samples K4 and K5 was analyzed from surface outcrop profiles. Previous research indicates that samples K4 and K5 are Middle Miocene in age and were deposited in a mangrove environment. Palynofacies identification from kerogen analysis indicates that sample K4 was deposited in an environment farther from the source of organic material, or in a mangrove environment in the lower deltaic plain, characterized by fine-to-very-fine carbonate sandstone. Conversely, sample K5 was deposited in an environment closer to the source of organic material, or in a mangrove environment in the upper deltaic plain, characterized by black shale with launau-clay lithology. Samples K4 and K5 have the same organic material composition, namely inertinite, vitrinite, and exinite, although the material sizes are different.